A clinical study of diagnostic efficacy of adenosine deaminase levels in tubercular pleural effusion - Bhushan, Mridul; Kumar, Rakesh; Nigam, P. (International Journal of Advances in Medicine, 2017)
Background: Tuberculosis is a common cause of pleural effusion in countries like India where it is highly endemic. However, the organism mycobacterium tuberculosis is seldom detectable in pleural fluid. The diagnosis of pleural tuberculosis has been greatly improved by the use of biochemical markers. The pleural fluid activity of adenosine deaminase (ADA) is one of the best providing reliable bases for a treatment decision, particularly in excluding the diagnosis of tuberculosis, due to its high sensitivity. The present study was aimed to evaluate the diagnostic efficacy of ADA levels in tubercular pleural effusion. Methods: The study is a clinical, prospective and observational study of 50 Patients of pleural effusion consecutively admitted in Government Medical College and Hospital, Kannouj from Dec 2008 to Dec 2009. Macroscopic findings, cytological, microbiological and biochemical analysis of pleural fluid were performed, including ADA levels in all patients. Results: Mean age group was 31 years and common in men. In our study, out of 30 patients with tuberculosis pleural fluid ADA was done in them and 28 (93.33%) of them had a level more than 40IU/L. Using a cut off of greater 40IU/L we got a sensitivity and specificity of 93.3% and 90% respectively and positive predictive value 93.3% and Negative predictive value 90%. Conclusions: All patients with TB pleural effusion had elevated ADA levels and there was a statistical significant association (p value <0.05) of ADA levels in differentiating TB pleural effusion from Non-TB pleural effusion.